Genetic testing, another important tool in presurgical evaluation of focal epilepsies in childhood - Rocio Garcia‐Uzquiano; Giulia Barcia; Emma Losito; Nicole Chemaly; Anna Kaminska; Isabelle Desguerre; Thomas Blauwblomme; Nathalie Boddaert; Rima Nabbout (Epilepsia Open, 2024)
Abstract Epilepsy surgery may be a curative therapy for patients with drug‐resistant epilepsies when focal lesions or foci are identified. Genetic testing is not yet routinely included in many presurgical evaluation programs although recent evidence support that finding a germline genetic mutation could help to better delineate the patient candidacy to surgery and provide valuable information on the expected surgery outcome. In this study, we report nine patients presenting drug‐resistant focal epilepsy enrolled in presurgical evaluation. We show how the identification of genetic pathogenic variant in epilepsy known genes led to the interruption of the presurgical work‐up and ruled out surgery in 7 of them. We observed that the co‐existence of some recurrent clinical characteristics as early seizures' onset, frequent precipitating factors including fever, and developmental delay or intellectual disability may be useful markers for germline genetic pathogenic variants. In this group, genetic assessment should be mandatory during presurgical work up, mainly in patients with negative magnetic resonance imaging (MRI) or doubtful structural lesions. The integration of next generation targeted sequencing into the presurgical evaluation can improve the selection of candidates for resective surgery and fosters a personalized medicine approach with a better outcome. Plaine Language Abstract Genetic testing is not yet systematically included in the pre‐surgical assessment of patients with drug‐resistant focal epilepsies. In this study, through the description of nine patients, we underline how the integration of genomics into the presurgical work up can help in evaluating the patient candidacy to surgery and provide valuable information on expected surgery outcome.